Application of the Friedman Test for Measuring Agriculture Financing by Commercial Banks in Haryana - Chikkara, Kuldip S.; Kodan, Anand S. (Indian Journal of Finance, 2012)
In this study, we have analyzed the trends and composition of agriculture credit as well as look into the comparative performance of all types of bank groups in agriculture financing in Haryana from 2000/2001 to 2008/2009 with the help of ACGR and Friedman's test. The Friedman's test indicates no significant difference between all three types of bank groups in disbursement of the 100 per cent allocation of agriculture credit limit and further, the study also express that all types of bank groups have not succeeded in disbursement of 100 per cent agriculture credit limit in the State during the period under consideration. Thus, it is a matter of concern for the policy makers of Haryana in general and agriculture development in particular.